Implementasi Metode Agile dalam Pengembangan Sistem E-document - Dio Leonardo Alexandes; Randika Aditio; Yuwan Jumaryadi (Journal of Information System Research (JOSH), 2022)
Documents are very important in a company or agency because they store various information, both general and confidential. At the West Jakarta Sub-Department of Highways there are problems in document management, the increasing number of documents that are received or received creates a buildup in document storage. Document storage is also carried out using a special document warehouse as a place to store documents. This problem can be solved by creating an electronic document repository. For this reason, in this study, researchers created a document management application that can be used to store documents electronically to the West Jakarta Highways Sub-dept. The application development process is carried out using agile methods starting from the stages of planning, implementation, software testing (testing), documentation, deployment, and maintenance (maintenance). The resulting application also has several features such as document search, document graphics, the number of documents that have been inputted, project documents and access rights. Based on the usability questionnaire that has been given, the developed application can assist in managing documents, and assist in storing and searching data.